Enhanced quantum yields by sterically demanding aryl-substituted β-diketonate ancillary ligands - Pittkowski, Rebecca; Strassner, Thomas (Beilstein Journal of Organic Chemistry, 2018)
Luminescent organometallic platinum(II) compounds are of interest as phosphors for organic light emitting devices. Their emissive properties can be tuned by variation of the ligands or by specific electron-withdrawing or electron-donating substituents. Different ancillary ligands can have a profound impact on the emission color and emission efficiency of these complexes. We studied the influence of sterically hindered, aryl-substituted β-diketonates on the emission properties of C^C* cyclometalated complexes, employing the unsubstituted methyl-phenyl-imidazolium ligand. The quantum yield was significantly enhanced by changing the auxiliary ligand from acetylacetonate, where the corresponding platinum(II) complex shows only a very weak emission, to mesityl (mes) or duryl (dur) substituted acetylacetonates. The new complexes show very efficient emission with quantum yields >70% in the sky-blue spectral region (480 nm) and short decay times (<3 μs).
Keywords: ancillary ligand; β-diketonates; photoluminescence; platinum(II) complex; quantum yield